RATE OF ANTIBIOTICS USE ACCORDING TO RATIONAL DRUG USE PROGRAM IN COMMUNITY HOSPITALS IN PHITSANULOK PROVINCE - Polnok, Assadang; Pengkum, Sangsuda; Polnok, Sanglar (Thai Bulletin of Pharmaceutical Sciences, 2025)
Rational drug use (RDU) is a key strategy in reducing antibiotic resistance. The Ministry of Public Health has established indicators and targets to promote the responsible use of antibiotics (RUA), particularly in four conditions: upper respiratory tract infections and acute bronchitis (URI), acute diarrhea (AD), fresh traumatic wounds (FTW), and prophylactic antibiotic use in normal vaginal delivery (APL). This study employed retrospective descriptive research conducted in eight community hospitals in Phitsanulok province. Data were collected from the Health Data Center system and the province’s RDU reports for the fiscal years 2018–2022. The results indicate that the antibiotic utilization rates for URI and APL decreased below the target threshold by the fiscal year 2022, with average rates of 8.61% and 6.57%, respectively. Meanwhile, the antibiotic use rate for AD also declined to 19.30%, meeting the target threshold of no more than 20%. However, the antibiotic prescription rate for FTW remained above the target, averaging 54.13%. The implementation of the Antibiotics Smart Use program in community hospitals in Phitsanulok province successfully reduced antibiotic utilization for URI, AD, and APL to meet the target level. However, adjustments in assessment criteria and additional measures are necessary to further reduce antibiotic use in FTW cases.